Conceptional framework to support vulnerable students during crisis, a real online learning experience during COVID-19 pandemic - Alrefaie, Zienab A. (International Journal Of Community Medicine And Public Health, 2021)
Coronavirus COVID-19 pandemic has caused psychological burden in terms of fear of the infection, anxiety and stress because of the spreading news about cases and deaths and even loneliness of the quarantine and curfew measures. Vulnerable students need support specially during times of crisis and this brief describes a framework to help such students. It is based on a real learning experience with a student who suffered loss of a family member in coincidence with the pandemic curfew measures just before being enrolled in the course. On the contrary to the beginning that seemed unpleasant, the current framework was implemented and effectively helped the end of the course to turn fruitful for the student.